Bending of elastic plates with micro-voids. (15th October 2018) - Repka, M.; Sladek, V.; Sladek, J.
Abstract: In this paper, we present a systematic development of unified formulation for bending of elastic plates with micro-voids. The homogenization concept is applied with replacing real medium with micro-voids by a homogeneous medium with effective material coefficients. The effective material coefficients are calculated in advance by solving properly selected micro-structural 3D boundary value problems in representative volume elements with specified shape and volume content of micro-voids. The unified formulation for plate bending problems is developed from 3D elasticity with taking into account the assumptions of three plate bending theories such as Kirchhoff-Love theory for bending of thin plates, 1st and 3rd order shear deformation theories for thick plates. Switching among these theories is allowed by proper selection of two key factors introduced in the unified formulation. The influence of the porosity on bending of porous plates subjected to transversal loading is studied via the numerical simulations.